2022
DOI: 10.1038/s41421-022-00388-0
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ phase separates with RXRα at PPREs to regulate target gene expression

Abstract: Peroxisome proliferator-activated receptor (PPAR)-γ is a key transcription activator controlling adipogenesis and lipid metabolism. PPARγ binds PPAR response elements (PPREs) as the obligate heterodimer with retinoid X receptor (RXR) α, but exactly how PPARγ orchestrates the transcriptional response is unknown. This study demonstrates that PPARγ forms phase-separated droplets in vitro and solid-like nuclear condensates in cell, which is intriguingly mediated by its DNA binding domain characterized by the zinc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…The LLPS paradigm provides a new framework to understand the mechanism underlying the physiological function of NRs. NRs that are known to undergo LLPS leading to the formation of MLOs or liquid droplets in vitro include AR [ 24 ], ER [ 26 ], GR [ 25 ], PPARγ [ 23 ] and RXRγ [ 27 , 28 ]. In different NRs, particular regions or domains with unique biochemical natures present different phase separation potentials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LLPS paradigm provides a new framework to understand the mechanism underlying the physiological function of NRs. NRs that are known to undergo LLPS leading to the formation of MLOs or liquid droplets in vitro include AR [ 24 ], ER [ 26 ], GR [ 25 ], PPARγ [ 23 ] and RXRγ [ 27 , 28 ]. In different NRs, particular regions or domains with unique biochemical natures present different phase separation potentials.…”
Section: Discussionmentioning
confidence: 99%
“…The structured domains of androgen receptor (AR), PPARγ and glucocorticoid receptor (GR) are the main drivers of LLPS. In particular, the formation of AR and PPARγ liquid condensates is mediated by DBD [ 23 , 24 ], whereas GR is mediated by LBD [ 25 ]. On the other hand, for the estrogen receptor (ER) and RXRγ, AB regions seem to be essential for condensate formation [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that although predominantly disordered, the AF-1 is characterized by transient long-range intramolecular contacts that can be enhanced by decreasing negative charge repulsion. Thus, a change in AF-1 structure and compaction could occur under cellular states that would affect protein net charge, such as the presence of binding partners including other proteins, nucleic acids (mRNA and chromatin), or small molecule metabolites 1 ; upon post-translational modification of PPARγ 42 ; or cellular compartments with localized changes in ionic strength or pH such as phase separated biomolecular condensates 43 .…”
Section: Discussionmentioning
confidence: 99%
“…These proteins heterodimerize with retinoid X receptor (RXR) and bind to a corepression complex of certain proteins. The heterodimers bind to a part of a gene area known as "peroxisome proliferator response elements (PPREs)" through their DNA binding domain (DBD) 2,3 .…”
Section: Introductionmentioning
confidence: 99%